Phloroglucinol Protects INS‐1 Pancreatic β‐cells Against Glucotoxicity‐Induced Apoptosis. (7th July 2015) - Park, Mi Hwa; Han, Ji Sook
Abstract : Decreasing numbers, and impaired function, of pancreatic β‐cells are key factors in the development of type 2 diabetes. This study was designed to investigate whether phloroglucinol protected pancreatic β‐cells against glucotoxicity‐induced apoptosis using a rat insulinoma cell line (INS‐1). High glucose treatment (30 mM) induced INS‐1 cell death; however, the level of glucose‐induced apoptosis was significantly reduced in cells treated with 100‐μM phloroglucinol. Treatment with 10–100‐μM phloroglucinol increased cell viability and decreased intracellular levels of reactive oxygen species, nitric oxide, and lipid peroxidation dose‐dependently in INS‐1 cells pretreated with high glucose. Furthermore, phloroglucinol treatment markedly reduced the protein expression of Bax, cytochrome c, and caspase 9, while increasing anti‐apoptotic Bcl‐2 protein expression. Cell death type was examined using annexin V/propidium iodide staining, revealing that phloroglucinol markedly reduced high glucose‐induced apoptosis. These results demonstrated that phloroglucinol could be useful as a potential therapeutic agent for the protection of pancreatic β‐cells against glucose‐induced apoptosis. Copyright © 2015 John Wiley & Sons, Ltd.